An analysis on the effects of the abolishment of the Emergency Ordinance 1969 and Internal Security Act 1960 / Muhamad Hazim Azman … [et al.] - Azman, Muhamad Hazim; Murshidi, Mohd Khalid; Samsul Hairi, Mohammad Na'im; Zainal Shah, Muhammad Amirul Shafiq (2014)
This research provides an analysis on the effect of the abolishment of Emergency Ordinance and Internal Security Act in Malaysia. These analyses focus on the issue whether the abolishment of laws without trial does give good effect or bad on the judicial and protecting society, as we know today. Detention without trial is also known as the preventive detention is a form of preventive measure executed by the government through the implemented laws in order to detain the person for the non-punitive purpose in the putative manner. Hence, the government can imprison a person without any criminal charge if the government thinks that the person has brought threats and harms to the unity and integrity of the nation. There were a few detention without trials law which have been repealed by the Parliament as examples the Emergency (Crime Prevention and Public Order) Ordinance 1969 and also the "ISA" 1960, which both these repelled laws will be emphasized as the subject of this proposal.